On the trajectory of discrimination: A meta-analysis and forecasting survey capturing 44 years of field experiments on gender and hiring decisions - Kouroutakis, Antonios (Science Direct, 2023)
A preregistered meta-analysis, including 244 effect sizes from 85 field audits and 361,645 individual job ap plications, tested for gender bias in hiring practices in female-stereotypical and gender-balanced as well as malestereotypical jobs from 1976 to 2020. A “red team” of independent experts was recruited to increase the rigor and robustness of our meta-analytic approach. A forecasting survey further examined whether laypeople (n = 499 nationally representative adults) and scientists (n = 312) could predict the results. Forecasters correctly antic ipated reductions in discrimination against female candidates over time. However, both scientists and laypeople overestimated the continuation of bias against female candidates. Instead, selection bias in favor of male over female candidates was eliminated and, if anything, slightly reversed in sign starting in 2009 for mixed-gender and male-stereotypical jobs in our sample. Forecasters further failed to anticipate that discrimination against male candidates for stereotypically female jobs would remain stable across the decades.
Keywords: Gender; Discrimination; Field experiments; Meta-analysis; Open science Forecasting; 63 Sociología::6307 Cambio y desarrollo social::6307.03 Política social; ODS 5 - Igualdad de género